Cervantes' Persiles and the travails of romance - Brownlee, Marina Scordilis (Toronto Iberic, 2019)
"This collection of original essays presents new ways of looking at Cervantes' final novel. Persiles, a work that engages with geopolitical models of race, ethnicity, nation, and religion, takes its inspiration from the highly influential Ethiopian Story (the Aithiopika) of Heliodorus. With particular relevance to the period, the Persiles questions the issue of cultural pluralism in the Spanish empire and emphasizes the need to rethink the radically altered category of lo bárbaro/the barbarian (which included not only the Jew, the Muslim, and the Gypsy, but also the criollo, the mestizo, and the indiano), a new multiracial and multiethnic reality that posed a profound challenge to early modern Spain. The contributors offer a range of perspectives in spatial theory, psychology and subjectivity, visual culture, and literary theory."--